49.0k views
2 votes
Given the function f, find

f(−3), f(3), f(−a), −f(a), f(a + h).
f(x) = 2x − 7
f(−3) =

f(3) =

f(−a) =

−f(a) =

f(a + h) =

User Vollie
by
4.8k points

2 Answers

2 votes

Answer:

f(x) =2x - 7

f( - 3) = 2( - 3) - 7 = - 13

f(3) = 2(3) - 7 = - 1

f(a) = 2a - 7

- f(a) = - (2a - 7) = 7 - 2a

f(a + h) = 2(a + h) - 7 = 2a + 2h - 7

Explanation:

User Johan Kronberg
by
5.5k points
3 votes

Answer:

Explanation:

f(x) =2x - 7

f( - 3) = 2( - 3) - 7 = - 13

f(3) = 2(3) - 7 = - 1

f(a) = 2a - 7

- f(a) = - (2a - 7) = 7 - 2a

f(a + h) = 2(a + h) - 7 = 2a + 2h - 7

User Roman Kishchenko
by
5.0k points